“A prisoner of El Frontón has been elected deputy”.: The political prisoners and the presidential elections of 1963 - Álvarez Alderete, Antenor (2019)
This paper addresses political participation in the general elections of 1963. But a central item in the analysis are the previous trajectories of political opponents, those who sought social justice (from different party tendencies), which for that reason were persecuted and imprisoned, whom we call political prisoners or political prisoners. In this sense, we will know about the life of professor and lawyer Genaro Ledesma Izquieta, who, being in prison, was elected deputy with the same rules imposed by the Military Government.